Alternative Growth Promoters Modulate Broiler Gut Microbiome and Enhance Body Weight Gain - Salaheen, Serajus; Kim, Seon-Woo; Haley, Bradd J.; Van Kessel, Jo Ann S.; Biswas, Debabrata (Frontiers in Microbiology, 2017)
Antibiotic growth promoters (AGPs) are frequently used to enhance weight-gain in poultry production. However, there has been increasing concern over the impact of AGP on the emergence of antibiotic resistance in zoonotic bacterial pathogens in the microbial community of the poultry gut. In this study, we adopted mass-spectrophotometric, phylogenetic, and shotgun-metagenomic approaches to evaluate bioactive phenolic extracts (BPE) from blueberry (Vaccinium corymbosum) and blackberry (Rubus fruticosus) pomaces as AGP alternatives in broilers. We conducted two trials with 100 Cobb-500 broiler chicks (in each trial) in four equal groups that were provided water with no supplementation, supplemented with AGP (tylosin, neomycin sulfate, bacitracin, erythromycin, and oxytetracycline), or supplemented with 0.1 g Gallic acid equivalent (GAE)/L or 1.0 g GAE/L (during the last 72 h before euthanasia) of BPE for six weeks. When compared with the control group (water only), the chickens supplemented with AGP and 0.1 g GAE/L of BPE gained 9.5% and 5.8% more body weight, respectively. The microbiomes of both the AGP- and BPE-treated chickens had higher Firmicutes to Bacteroidetes ratios. AGP supplementation appeared to be associated with higher relative abundance of bacteriophages and unique cecal resistomes compared with BPE supplementation or control. Functional characterization of cecal microbiomes revealed significant animal-to-animal variation in the relative abundance of genes involved in energy and carbohydrate metabolism. These findings established a baseline upon which mechanisms of plant-based performance enhancers in regulation of animal growth can be investigated. In addition, the data will aid in designing alternate strategies to improve animal growth performance and consequently production.